Income related health inequalities associated with Covid 19 pandemic in South Africa: evidence from wave 4. - Zulu, Abongile (University of the Witwatersrand, Johannesburg, 2023)
Even though there have been some observable significant developments within the average level of diseases and rates of mortalities in many nations (developed and developing), health inequalities that exist within and between various nations, within social groupings and different religious groups have expanded in the last years (CSDH/WHO, 2007). Respectively, this increase in health inequalities has been a growing concern for many governments across the world. Also, civil society organisations and other organisations operating internationally have been more concerned on how they would go about reducing these inequalities (CSDH/WHO, 2007). On this point, the World Health Organisation has noted previously that the most efficient way for health care sector to contribute to the lessening or reduction of disparities existing in health is by establishing a good systems and procedures of primary health care. The contribution of a well established primary health care system is through the realization of various mediations in order to deal with the social determining factors, and these are social and economic conditions that are inclusive of the health care system structure that is influenced by resources, power and the distribution of money that consequently influence separate and group differences existing within the status of health (Burger & Christian, 2018). The most recent available evidence suggests that primary health care principles and values, equity in health, people centred care and subsequently a most important part for communities in health action can answer to the prospects and challenges faced by the modern-day societies (NICD, 2020)
A Research Report submitted in partial fulfillment of the Degree of Master of Commerce (Applied Development Economics) in the School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Income; Health inequality; Health; Covid -19; South Africa; UCTD; SDG-8: Decent work and economic growth